Wordsworth a poet of nature - Toothaker, Myrtle (My University, 1902)
Introduction: In the “Prelude” Wordsworth gives the story of his life, or growth of the poet’s mind. It is an autobiographical poem written by himself. It was begun in the year 1799 and finished in 1805. The reason that we study the Prelude is because no other production gives us so deep, and sustained a view of his feelings about nature, and of the relation which he believed to exist between nature and the soul of man. In his mental history two periods are especially prominent first his school time at Hawkshead, Esthwaite Lake, eight years in all. This was the springtime of his soul, a fair springtime in which all the young impulses, and intuitions were first awakened, when the laid in, and deeply engrained into every fiber of his being.
Citation: Toothaker, Myrtle. Wordsworth a poet of nature. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Wordsworth; Poetry; English; Nature; Theses; Manuscripts (documents)